Arm circumference: its importance for dialysis patients in the obesity era - (:unkn) unknown (SPRINGER, 2013)
The purposes of this study were to investigate the association between arm circumference and body mass index (BMI) and to discuss problems, mainly arm circumference and cuff size mismatch, that could affect the reliability of home blood pressure monitoring (HBPM) among peritoneal dialysis (PD) and hemodialysis (HD) patients. 525 PD and 502 HD patients from 16 centers were included in the study. A two-part questionnaire was used to gather information from the participants. Arm circumferences were categorized into four groups according to the British Hypertension Society cuff size recommendations. Mean BMI and arm circumference of all participants were 25.0 kg/m(2) and 27.6 cm, respectively. There was a significant correlation between BMI and arm circumference. The mean BMI and arm circumference values were higher in PD patients than in HD patients. Requirement of a large-sized adult cuff was more common among PD patients compared to HD patients (14 % vs 8 %, p = 0.002). Since HBPM is a useful tool for clinicians to improve BP control, nephrologists should be aware of the problems related to HBPM in dialysis patients and take an active role to increase the reliability of HBPM.
Keywords: Arm circumference; Cuff; Hemodialysis; Home blood pressure monitoring; Obesity; Peritoneal dialysis; BLOOD-PRESSURE-MEASUREMENT; PROTOCOL REVISION 2010; EUROPEAN-SOCIETY; INTERNATIONAL PROTOCOL; HOME SPHYGMOMANOMETERS; HEMODIALYSIS PATIENTS; JAPANESE SOCIETY; BODY-MASS; HYPERTENSION; VALIDATION